Strategi Guru dalam Melaksanakan Pembelajaran Luar Jaringan Masa Pandemi COVID-19 di Kelas IV C Sekolah Dasar Negeri I Kota Bengkulu - Perdi ansyah; Osa Juarsa; Pebrian Tarmizi (Universitas Bengkulu, 2022)
This study aims to describe the teacher's strategy in implementing offline learning during the COVID-19 pandemic related to preliminary activities, core learning activities, and closing activities for offline learning in class IV C of SD Negeri 1 Bengkulu City. This research uses descriptive qualitative research. The data used in this study are primary data and secondary data. The research instrument used observation and interview guidelines. The data analysis technique uses the steps, namely, data collection, data condensation, data presentation, and concluding. The validity of the data used triangulation and member check. The results showed that in carrying out learning outside the network during the COVID-19 pandemic in class IV C of SD Negeri 1 Bengkulu City in the preliminary learning activities, the teacher said greetings, invited students to pray, gave apperception, motivation, literacy, explained the general subject matter and explain the learning objectives. In the core learning activities, the teacher uses the Discovery Learning (DL) model, lecture and question and answer learning methods, audiovisual learning media, and lesson module teaching materials which contain material from thematic books K13 and there are also materials taken from Bupena. In closing learning activities, the teacher provides formative tests, feedback, follow-up, provides reinforcement, invites students to pray, and ends with saying greetings. Keywords: Descriptive Studies, Teacher Strategies, preliminary activities, core learning, closing learning